Nbs1‐mediated DNA damage repair pathway regulates haematopoietic stem cell development and embryonic haematopoiesis - Chen, Yu; Sun, Jie; Ju, Zhenyu; Wang, Zhao‐Qi; Li, Tangliang (Cell proliferation, 2021)
Objectives DNA damages pose threats to haematopoietic stem cells (HSC) maintenance and haematopoietic system homeostasis. Quiescent HSCs in adult mouse bone marrow are resistant to DNA damage, while human umbilical cord blood‐derived proliferative HSCs are prone to cell death upon ionizing radiation. Murine embryonic HSCs proliferate in foetal livers and divide symmetrically to generate HSC pool. How murine embryonic HSCs respond to DNA damages is not well‐defined. Materials and methods Mice models with DNA repair molecule Nbs1 or Nbs1/p53 specifically deleted in embryonic HSCs were generated. FACS analysis, in vitro and in vivo HSC differentiation assays, qPCR, immunofluorescence and Western blotting were used to delineate roles of Nbs1‐p53 signaling in HSCs and haematopoietic progenitors. Results Nbs1 deficiency results in persistent DNA breaks in embryonic HSCs, compromises embryonic HSC development and finally results in mouse perinatal lethality. The persistent DNA breaks in Nbs1 deficient embryonic HSCs render cell cycle arrest, while driving a higher rate of cell death in haematopoietic progenitors. Although Nbs1 deficiency promotes Atm‐Chk2‐p53 axis activation in HSCs and their progenies, ablation of p53 in Nbs1 deficient HSCs accelerates embryonic lethality. Conclusions Our study discloses that DNA double‐strand repair molecule Nbs1 is essential in embryonic HSC development and haematopoiesis. Persistent DNA damages result in distinct cell fate in HSCs and haematopoietic progenitors. Nbs1 null HSCs tend to be maintained through cell cycle arrest, while Nbs1 null haematopoietic progenitors commit cell death. The discrepancies are mediated possibly by different magnitude of p53 signaling. Genetic deletion of Nbs1, a DNA double‐strand break repair molecule, in murine embryonic haematopoietic stem cells (HSCs) generates persistent DNA damages in HSCs and their progenies, contributing to defective haematopoiesis and perinatal lethality in mice. Nbs1 null HSCs and haematopoietic progenitors show different cell fate, which could be mediated by differential magnitude of p53 signaling in each cell population. Intriguingly, p53 loss accelerates lethality of mice with Nbs1 deletion in HSCs, indicating an essential role of p53 signaling safeguarding embryonic haematopoiesis.